Pengaruh penambahan jenis dan konsentrasi hidrokoloid terhadap sifat fisik dan kualitas pemasakan mie kering bebas gluten - Nurmiati, Nurmiati; Patimang, Andi; Nirwana, Nirwana (Politeknik Pertanian Negeri Pangkajene Kepulauan, 2025)
Noodles are a food product that is often consumed by Indonesian people. The main ingredient in making noodles is flour which contains gluten which is one of the causes of celiac disease. Therefore, gluten-free noodles are made from local flour, namely sago starch, yellow sweet potato flour and green beans. The addition of hydrocolloids is done to resemble the characteristics of noodles in general. The aim of the research was to determine the effect of adding guar gum and xanthan gum on the physical properties and cooking quality of dry gluten-free noodles. This research was carried out experimentally with qualitative and quantitative approaches using a Completely Randomized Factorial Design. The results of research on the molding ability of noodles in general are that the dough is not yet perfectly formed, but it can be molded, even though the noodles are still broken. The visual appearance of dry gluten-free noodles is brownish yellow. The concentration of xanthan gum and guar gum has a significant effect (α≤0.05) on the moisture produced. The concentration of xanthan gum and guar gum has a significant effect (α≤0.05) on the resulting cooking time and the type of hydrocolloid xanthan gum and guar gum has a significant effect (α≤0.05) on the resulting water absorption capacity, cooking loss and cooking time.